2013
DOI: 10.1002/syn.21663
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of vesicular monoamine transporter 2 in epileptic patients and experimental rats

Abstract: In the central nervous system (CNS), vesicular monoamine transporter 2 (VMAT2) transports cytoplasmic monoamines such as dopamine into synaptic vesicles for storage and subsequent exocytotic release. Recent studies have provided direct evidence for VMAT2-regulated monoamine neurotransmitter involvement in the neurophysiological activities of neurological disease. This study investigated the expression pattern of VMAT2 in patients with temporal lobe epilepsy (TLE) and in a rat model of epilepsy. We assessed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Taking previously mentioned studies into account, it is suggested that the transiently increased VMAT2 might be a compensatory response to enhance monoaminergic neurotransmission to counteract hyperexcitability and epileptic seizures. The decrease in VMAT2 expression after SRS is consistent with the known involvement of monoaminergic alterations in epileptic co-morbidities, such as anxiety and depression, and might contribute to the epilepsy disease progression (Jiang et al, 2013). …”
Section: Slc18 Familysupporting
confidence: 78%
See 2 more Smart Citations
“…Taking previously mentioned studies into account, it is suggested that the transiently increased VMAT2 might be a compensatory response to enhance monoaminergic neurotransmission to counteract hyperexcitability and epileptic seizures. The decrease in VMAT2 expression after SRS is consistent with the known involvement of monoaminergic alterations in epileptic co-morbidities, such as anxiety and depression, and might contribute to the epilepsy disease progression (Jiang et al, 2013). …”
Section: Slc18 Familysupporting
confidence: 78%
“…Moreover, the expression level of VMAT2 mRNA and protein has been determined in resected neocortices of TLE patients (Jiang et al, 2013) and in the hippocampus and adjacent cortices of rats in different stages of the post-SE pilocarpine model (Jiang et al, 2013). VMAT2 is transiently increased in the acute stage after pilocarpine-induced epileptic seizures, but its expression is clearly decreased after SRS in the hippocampus and temporal lobe cortices of TLE rats.…”
Section: Slc18 Familymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we identified homozygous loss of function alleles in three genes with proposed roles in synaptic transmission: SLC18A 2, CPLX1 , and SNX14 . Abnormal expression of VMAT2, encoded by SLC18A2, has been proposed to contribute to vulnerability toward epilepsy-related psychiatric disorders and cognitive impairment (Jiang et al, 2013). Our finding complements the single report in the literature of a homozygous missense mutation in this gene and provides our patient possible direct route to treatment with dopamine agonists as described (Rilstone et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis of HIF‐1α immunoreactivity was performed as described previously (Jiang et al, ). Total protein was extracted according to the manufacturer's instructions (Keygen Biotech, Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%